ENGARUH KONSELING TENTANG KEPUTIHAN TERHADAP TINGKAT PENGETAHUAN KEPUTIHAN PADA PEREMPUAN DI WILAYAH KERJA PUSKESMAS II BATURADEN - Anggraeni Dwi Pamulatsih; Tin Utami (Viva Medika, 2015)
Health problems are common genital area in women is vaginal discharge. Asmany as 75% of women in the world have suffered from pathological vaginaldischarge. Indonesian women are more prone to reproductive tract infections(RTI) such as flour albus (white) in Indonesia picucuaca moist. Based on theresults of preliminary studies conducted by researchers, the results obtained in2013 the number of cases of pathological vaginal discharge as many as 953 cases,consisting of as many as 458 cases BV, trichomoniasis as 6 cases and 489 cases ofcandidiasis.This research method is pre exsperimental design using the approach of one grouppretest - posttest. Data collection techniques using primary data obtained fromrespondents directly, secondary data in the study include the initials ofrespondents, data on the number of women who mengalamikeputihan. Thesampling technique used purposive sampling 91sampel.The results showed that the results of the univariate analysis showed that priorknowledge of counseling average of 91 respondents was as much as 59.9 wherethe score is included in a sufficient knowledge. While after counseling the averageamount of knowledge amounted to 71.7 is included in the score range sufficientknowledge.Bivariate analysis results showed that there was an effect of counseling ondischarge thitung (-10.424) <- ttable (-1.6620) and Sig value 0.000 <0.1 it can beconcluded that Ho is rejected, meaning that the average knowledge before andafter counseling is different (no influence).The conclusion of this study that there was an effect of counseling on dischargegiven to women to the level of knowledge that increased scores but are stillincluded in the knowledge enough.Keywords: Counseling, Whitish, Knowledge Level, Woman